Psychometric Properties of the Arabic Version of the Mindfulness in Teaching Scale - Almeqdadi, Farouq; Al-Shurafat, Saleh Swalem; Afari, Ernest; Khine, Myint Swe (Dirasat: Educational Sciences, 2024)
Objectives: Interest in Mindfulness in several professions including teaching has increased. To develop the techniques and methods based on mindfulness, several research papers were carried on this topic in teaching according to a comprehensive definition that takes into account awareness, memory and retention to describe a variety of teaching practices, processes and features. Methods: The original version of the Mindfulness in Teaching Scale (MTS) was in English. The researchers translated it into Arabic and administered it to a sample of 554 Jordanian teachers. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) supported a two-factor structure (teacher intrapersonal mindfulness and teacher interpersonal mindfulness) as proposed by the scale’s authors. Results: The results have demonstrated that the Arabic version of the mindfulness in teaching scale consisting of 14 items and two subscales is valid and reliable for teachers in Arabic speaking countries. The means, standard deviations, skewness, and kurtosis of the MTS-A items were obtained. Mean and standard deviation values ​​ranged from 1.58 to 3.65 and 0.841 to 1.21, respectively, indicating a narrow dispersion in participant responses around the mean. Conclusions: The primary goal was to assess the MTS-A's validity and reliability among teachers in Jordan. With 9 items representing teachers' intrapersonal mindfulness and 5 items indicating teachers' interpersonal mindfulness, the 14-item two-factor CFA demonstrated that the model fit the data well. The findings show that the Arabic mindfulness in teaching scale, which consists of 14 questions and two subscales, is valid and trustworthy for use by instructors in Arabic-speaking regions.